Reputation:
Question:
A class SeriesSum is designed to calculate the sum of the following series:
Class name : SeriesSum
Data members/instance variables:
x : to store an integer number
n : to store number of terms
sum : double variable to store the sum of the series
Member functions:
SeriesSum(int xx, int nn) : constructor to assign x=xx and n=nn
double findfact(int m) to return the factorial of m using recursive technique.
double findpower(int x, int y) : to return x raised to the power of y using recursive technique.
void calculate( ) : to calculate the sum of the series by invoking the recursive functions respectively
void display( ) : to display the sum of the series
(a) Specify the class SeriesSum, giving details of the constructor(int, int), double findfact(int), double findpower(int, int), void calculate( ) and void display( ).
Define the main( ) function to create an object and call the functions accordingly to enable the task.
Code:
class SeriesSum
{
int x,n;
double sum;
SeriesSum(int xx,int nn)
{ x=xx;
n=nn;
sum=0.0;
}
double findfact(int a)
{ return (a<2)? 1:a*findfact(a-1);
}
double findpower(int a, int b)
{ return (b==0)? 1:a*findpower(a,b-1);
}
void calculate()
{ for(int i=2;i<=n;i+=2)
sum += findpower(x,i)/findfact(i-1);
}
void display()
{ System.out.println("sum="+ sum);
}
static void main()
{ SeriesSum obj = new SeriesSum(3,8);
obj.calculate();
obj.display();
}
}
MyProblem:
I am having problems in understanding that when i= any odd number (Taking an example such as 3 here)then it value that passes through findfact is (i-1)=2 then how am I getting the odd factorials such as 3!
Any help or guidance would be highly appreciated.
Optional:
If you can somehow explain the recursion taking place in the findpower and findfactorial,it would be of great help.
Upvotes: 0
Views: 2959
Reputation: 2037
I'm not sure I understand your question correctly, but I try to help you the best I can.
In this code i never will be any odd number
for(int i=2;i<=n;i+=2)
i will be: 2 , 4 , 6 , 8 and so on because i+=2
The findfact() function in a more readable version:
double findfact(int a){
if(a < 2 ){
return 1;
} else {
return a * findfact(a - 1);
}
}
you can imagine it as a staircase, every call of findfact is a step:
We test: if a < 2 then return 1 else we call findfact()
again with a-1
and multiply a
with the result of findfact()
The same function without recursion:
double findfact(int a){
int sum = 1;
for(int i = a; i > 0; i--){
sum *= i;
}
return sum;
}
Same by the findpower function:
if b == 0 then return 1 else call findpower()
with a, b-1
and multiply the return value of findpower()
with a
So the last called findpower() will return 1
(b = 0)
The second last findpower() will return a * 1
(b = 1)
The third last findpower() will return a * a * 1
(b = 2)
so you can see findpower(a, 2) = a * a * 1 = a^2
Hope I could help you
Upvotes: 1
Reputation: 186668
You can simplify the summation and get rid of power and factorial. Please notice:
x * x
item == x ** (2 * n) / (2 * n - 1)!
the next one will be item * x * x / (2 * n) / (2 * n + 1)
.Implementation:
private static double sum(double x, int count) {
double item = x * x; // First item
double result = item;
for (int i = 1; i <= count; ++i) {
// Next item from previous
item = item * x * x / (2 * i) / (2 * i +1);
result += item;
}
return result;
}
In the real world, you can notice that
sinh(x) = x/1! + x**3/3! + x**5/5! + ... + x**(2*n - 1) / (2*n - 1)! + ...
and your serie is nothing but
x * sinh(x) = x**2/1! + x**4 / 3! + ... + x**(2*n) / (2*n - 1)! + ...
So you can implement
private static double sum(double x) {
return x * (Math.exp(x) - Math.exp(-x)) / 2.0;
}
Upvotes: 0
Reputation: 153
Try to run below code, it will clear all your doubts (i have modified some access specifier and created main method)
public class SeriesSum
{
int x,n;
double sum;
SeriesSum(int xx,int nn)
{ x=xx;
n=nn;
sum=0.0;
}
double findfact(int a)
{ return (a<2)? 1:a*findfact(a-1);
}
double findpower(int a, int b)
{ return (b==0)? 1:a*findpower(a,b-1);
}
void calculate()
{
System.out.println("x ="+x);
System.out.println("n ="+n);
for(int i=2;i<=n;i+=2){
System.out.println(x+"^"+i+"/"+(i-1)+"!" +" = " +(findpower(x,i)+"/"+findfact(i-1)) );
//System.out.println(findpower(x,i)+"/"+findfact(i-1));
sum += findpower(x,i)/findfact(i-1);
}
}
void display()
{ System.out.println("sum="+ sum);
}
public static void main(String arg[])
{ SeriesSum obj = new SeriesSum(3,8);
obj.calculate();
obj.display();
}
}
// ----- output ----
x =3
n =8
3^2/1! = 9.0/1.0
3^4/3! = 81.0/6.0
3^6/5! = 729.0/120.0
3^8/7! = 6561.0/5040.0
sum=29.876785714285713
Upvotes: 0
Reputation: 2613
Take a closer look a the loop. i
starts at 2 and is incremented by 2 every iteration, so it is never odd. It corresponds to the successive powers of x
, each of which is divided by the factorial of i -1
(which IS odd).
As for the recursion in findfact
, you just need to unwrap the first few calls by hand to see why it works :
findfact(a) = a * findfact(a -1)
= a * (a - 1) * findfact(a -2)
= a * (a - 1) * (a - 2) * findfact(a - 3)
...
= a * (a - 1) * (a - 2) * ... * 2 * findfact(1)
= a * (a - 1) * (a - 2) * ... * 2 * 1
= a!*
The same reasoning works with findpower
.
As a side note, while it may be helpful for teaching purposes, recursion is a terrible idea for computing factorials or powers.
Upvotes: 1